Radiación fotosintéticamente activa y propiedades fisico-químicas en suelos forestales con y sin incendio - Maycotte Morales, Carlos César; Velázquez Martínez, Alejandro; Vargas Hernández, J. Jesús; Trinidad Santos, Antonio; Musálem Santiago, Miguel Ángel; Vera Castillo, Gil (Instituto de Ecología, A.C., 2016)
The effect of fire on the increment of photosynthetic active radiation and physical and chemical properties in soils was evaluated during late winter 1999 and early spring 2000 in Zacualtipán, Hidalgo, in a Pinus patula forest that was affected by fire in the spring of 1998. The data showed that radiation increased drastically in the burned stand, considering that radiation incidence was homogeneous along the slope in both stands. Fire did not modify soil texture, pH, inorganic nitrogen, potassium, magnesium, iron, copper, zinc, manganese and cation exchange capacity. After a six month period, soil organic matter, potassium and magnesium increased again up to similar levels as in the unburned stand. Fire also modified the spatial pattern of some ions such as iron, zinc, manganese, and copper. Initially, these ions did not show a spatial trend in concentration, but after a six month period, they tended to increase their concentration in the lower elevation sites.